PCSK9 Association With Lipoprotein(a). Issue 1 (24th June 2016) - Tavori, Hagai; Christian, Devon; Minnier, Jessica; Plubell, Deanna; Shapiro, Michael D.; Yeang, Calvin; Giunzioni, Ilaria; Croyal, Mikael; Duell, P. Barton; Lambert, Gilles; Tsimikas, Sotirios; Fazio, Sergio
Abstract : Rationale: : Lipoprotein(a) [Lp(a)] is a highly atherogenic low-density lipoprotein–like particle characterized by the presence of apoprotein(a) [apo(a)] bound to apolipoprotein B. Proprotein convertase subtilisin/kexin type 9 (PCSK9) selectively binds low-density lipoprotein; we hypothesized that it can also be associated with Lp(a) in plasma. Objective: : Characterize the association of PCSK9 and Lp(a) in 39 subjects with high Lp(a) levels (range 39–320 mg/dL) and in transgenic mice expressing either human apo(a) only or human Lp(a) (via coexpression of human apo(a) and human apolipoprotein B). Methods and Results: : We show that PCSK9 is physically associated with Lp(a) in vivo using 3 different approaches: (1) analysis of Lp(a) fractions isolated by ultracentrifugation; (2) immunoprecipitation of plasma using antibodies to PCSK9 and immunodetection of apo(a); (3) ELISA quantification of Lp(a)-associated PCSK9. Plasma PCSK9 levels correlated with Lp(a) levels, but not with the number of kringle IV-2 repeats. PCSK9 did not bind to apo(a) only, and the association of PCSK9 with Lp(a) was not affected by the loss of the apo(a) region responsible for binding oxidized phospholipids. Preferential association of PCSK9 with Lp(a) versus low-density lipoprotein (1.7-fold increase) was seen in subjects with high Lp(a) and normal low-density lipoprotein. Finally, Lp(a)-associated PCSK9 levels directly correlated with plasma Lp(a) levels but not with total plasma PCSK9 levels. Conclusions: : Our results show, for the first time, that plasma PCSK9 is found in association with Lp(a) particles in humans with high Lp(a) levels and in mice carrying human Lp(a). Lp(a)-bound PCSK9 may be pursued as a biomarker for cardiovascular risk. Abstract : Supplemental Digital Content is available in the text.